2024
DOI: 10.3390/jintelligence12010004
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Learning Reactivity on Item-Specific and Relational Processing

Minyu Chang,
Charles Brainerd

Abstract: Judgments of learning (JOLs) reactivity refers to the finding that the mere solicitation of JOLs modifies subsequent memory performance. One theoretical explanation is the item-specific processing hypothesis, which posits that item-level JOLs redound to the benefit of later memory performance because they enhance item-specific processing. The current study was designed to test this account. We factorially manipulated the organization (blocked vs. randomized) of categorized lists and JOL condition (item-JOLs, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…During the process of word encoding, making JOLs increases the metacognitive monitoring process (Lei et al 2020) and thus enhances learning engagement (Shi et al 2023). Additionally, searching for cues to inform JOL formation also enhances item-specific processing (Chang and Brainerd 2024;Senkova and Otani 2021;Zhao et al 2023aZhao et al , 2023b, thus producing more elaborative processing. Cognitive neural activities related to learning engagement (alpha ERD) and those related to elaborative encoding (LPC amplitude and beta ERD) together contribute to the generation of the positive reactivity effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of word encoding, making JOLs increases the metacognitive monitoring process (Lei et al 2020) and thus enhances learning engagement (Shi et al 2023). Additionally, searching for cues to inform JOL formation also enhances item-specific processing (Chang and Brainerd 2024;Senkova and Otani 2021;Zhao et al 2023aZhao et al , 2023b, thus producing more elaborative processing. Cognitive neural activities related to learning engagement (alpha ERD) and those related to elaborative encoding (LPC amplitude and beta ERD) together contribute to the generation of the positive reactivity effect.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between reactivity and level of processing suggests that the reactivity effect may result from the fact that making JOLs induces more elaborative processing. Furthermore, it has been shown that making JOLs promotes item-specific processing of study items, in turn producing superior recall or recognition performance (Chang and Brainerd 2024;Senkova and Otani 2021;Zhao et al 2023aZhao et al , 2023b.…”
Section: Putative Mechanismsmentioning
confidence: 99%